Is there potential for repurposing statins as novel antimicrobials? - Hennessy, E.; Adams, C.; Reen, F.; O'Gara, Fergal (American Society for Microbiology, 2016)
Copyright © 2016, American Society for Microbiology. All Rights Reserved.Statins are members of a class of pharmaceutical widely used to reduce high levels of serum cholesterol. In addition, statins have so-called "pleiotropic effects," which include inflammation reduction, immunomodulation, and antimicrobial effects. An increasing number of studies are emerging which detail the attenuation of bacterial growth and in vitro and in vivo virulence by statin treatment. In this review, we describe the current information available concerning the effects of statins on bacterial infections and provide insight regarding the potential use of these compounds as antimicrobial therapeutic agents.